2022
DOI: 10.21037/tau-22-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy evaluation of thickened condom in the treatment of premature ejaculation

Abstract: Background: This study aimed to evaluate the efficacy of thickened condoms in the treatment of premature ejaculation.Methods: From August to December 2021, patients with premature ejaculation treated in the Urology and Andrology Center of the First Affiliated Hospital of Medical College of Zhejiang University were selected for a clinical controlled study. A total of 100 patients with premature ejaculation were enrolled as the premature ejaculation group and 30 normal men as the control (normal married men, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was found that the ejaculation latency time was signi cantly prolonged after the use of thickened condoms in patients with premature ejaculation. 15 In a prevalence study conducted by Waldinger et al, premature ejaculation rates, IELT times and condom use were evaluated in men in the ve countries included in the study. In the study, in which approximately 500 patients were evaluated, it was determined that 29% of the patients used condoms.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the ejaculation latency time was signi cantly prolonged after the use of thickened condoms in patients with premature ejaculation. 15 In a prevalence study conducted by Waldinger et al, premature ejaculation rates, IELT times and condom use were evaluated in men in the ve countries included in the study. In the study, in which approximately 500 patients were evaluated, it was determined that 29% of the patients used condoms.…”
Section: Resultsmentioning
confidence: 99%
“…• For some men, wearing thicker condoms can help prevent premature ejaculation by reducing sensitivity in the penis and improving penile erection [13].…”
Section: Advantagesmentioning
confidence: 99%
“…• Condoms can tear or break during intercourse and may result in an unwanted pregnancy or exposure to STIs. Some of the factors associated with condom breakage are excessive friction during sex, longer duration of intercourse, incorrect usage, using the wrong size, use of oil-based lubricants, and reuse of condoms [9,13,14]. Oil-based lubricants can impair the integrity of latex condoms [9].…”
Section: Disadvantagesmentioning
confidence: 99%